Netzneutralität: Regulierungsbedarf? - Hubertus Gersdorf (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2011)
In principle, all data on the Internet have so far been transmitted on the basis of best-effort, i.e. equally and without change, regardless of content, service, application, origin or destination. Quality of Service (QoS) has not been excluded, but has instead generally been limited to the access network of the Internet Service Provider (access-ISP) (IPTV, VoIP etc.). Now, the ISPs plan to offer such a QoS on the Internet as well by means of various prioritised transport groups. These QoS transport groups are not supposed to displace, but rather to complement the best effort area (QoS and best effort). Hereby the ISP first expect to participate more in the added value of the Internet. Secondly, the problems caused by the bottleneck for time-critical services and other forms of QoS (IPTV, VoIP, gaming etc.) are to be eliminated. Thirdly, various transport groups and various groups of products (IPTV, VOD, interactive services such as gaming etc.) characterised by specific technical features of performance and features of quality are to be composed and marketed by the ISP to the content provider, to the service provider and to the consumer. In order to guarantee such QoS on the Internet, the ISP have to agree on crossnetwork technical standards for QoS.
Keywords: 330; Internet; Service Provider; Netzzugang; Dienstleistungsqualität; Regulierung